STUDY OF EPOXIDE DECYCLISATION OF CARYOPHYLENE OXIDE WITH SYNTHETIC ZEOLITE AS CATALYSTS - Winarto Haryadi; M. Muchalal (Indonesian Journal of Chemistry, 2004)
The reaction of epoxide ring opening of caryophillene oxide has been done using zeolite H-Y, H-sodalit, and H-ZSM-5 as catalysts. The reactions were done in two types, there were in dioxane solvent at temperature of 110 oC and without solvent at temperature of 175 oC. The catalyst weight was 10 % from caryophillene oxide weight, and the time of reaction was four hours. The product of reaction was analyzed using GC, FTIR, and GC-MS. The reactions of caryophillene oxide in dioxane solvent with the three kinds of zeolites did not give any targeted product. Whereas, the reactions without solvent gave three main products, there was one compound with one group of secondary hidroxyl (secondary alcohol), and two compounds of ketone from caryophillene. The reaction product of caryophillene oxide obtained without using solvent with the three type of catalysts were then compared. Conversion of three main products produced by H-ZSM-5 catalyst, H-sodalit catalyst and H-Y catalyst were 82.11 %, 54.92 % and 38.53 % respectively. For that reason, the transformation of caryophillene oxide using H-ZSM-5 catalyst was considered to be the best selective product. The alcohol product was resulted from reaction between caryophillene oxide and Bronsted acid, and  the ketone products was resulted from the reaction with Lewis acid in zeolite.